BL_GERICHTE 470 12 68 vom 15. März 2012 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Strafrecht vom 18. Juni 2012 (470 12 68) - BL Gerichte (2012)
Verfahrenseinstellung; Kostenentscheid